2016
DOI: 10.1371/journal.pone.0165670
|View full text |Cite
|
Sign up to set email alerts
|

Tripping Elicits Earlier and Larger Deviations in Linear Head Acceleration Compared to Slipping

Abstract: Slipping and tripping contribute to a large number of falls and fall-related injuries. While the vestibular system is known to contribute to balance and fall prevention, it is unclear whether it contributes to detecting slip or trip onset. Therefore, the purpose of this study was to investigate the effects of slipping and tripping on head acceleration during walking. This information would help determine whether individuals with vestibular dysfunction are likely to be at a greater risk of falls due to slipping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…However, nothing with mass can have an instantaneous acceleration change to achieve the theoretical step change. The fastest real head movements are achieved in ~5 to 10 ms (Arena et al 2016). For otoliths to follow such fast movement requires an underdamped system with light damping, to accurately report real-time acceleration.…”
Section: Damping Of Otolithic Systemsmentioning
confidence: 99%
“…However, nothing with mass can have an instantaneous acceleration change to achieve the theoretical step change. The fastest real head movements are achieved in ~5 to 10 ms (Arena et al 2016). For otoliths to follow such fast movement requires an underdamped system with light damping, to accurately report real-time acceleration.…”
Section: Damping Of Otolithic Systemsmentioning
confidence: 99%
“…The first step of such a response is recognising the onset of the perturbation, achieved though integration of visual, somatosensory and vestibular sensory information. The contribution of each sensory system may vary with perturbation type due to differences in the perception of motion [ 37 ]. Stability can then be recovered through a number of strategies, such as compensatory stepping, counter rotation or grasping actions [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is regarded as a fall impact. Various fall experiments have suggested that the acceleration value at impact is approximately 4-11 m/s 2 with different ranges depending on the type or direction of the fall [17]. It has been reported that impact acceleration of a backward fall is approximately 25% greater than that of a forward fall through kinematic analysis of human body segments [18].…”
Section: Introductionmentioning
confidence: 99%